Paediatric European Network for Treatment of AIDS (PENTA) guidelines for treatment of paediatric HIV‐1 infection 2015: optimizing health in preparation for adult life. Issue 1 (3rd February 2015) - Bamford, A; Turkova, A; Lyall, H; Foster, C; Klein, N; Bastiaans, D; Burger, D; Bernadi, S; Butler, K; Chiappini, E; Clayden, P; Della Negra, M; et al.
Abstract : The 2015 Paediatric European Network for Treatment of AIDS (PENTA) guidelines provide practical recommendations on the management of HIV‐1 infection in children in Europe and are an update to those published in 2009. Aims of treatment have progressed significantly over the last decade, moving far beyond limitation of short‐term morbidity and mortality to optimizing health status for adult life and minimizing the impact of chronic HIV infection on immune system development and health in general. Additionally, there is a greater need for increased awareness and minimization of long‐term drug toxicity. The main updates to the previous guidelines include: an increase in the number of indications for antiretroviral therapy (ART) at all ages (higher CD4 thresholds for consideration of ART initiation and additional clinical indications), revised guidance on first‐ and second‐line ART recommendations, including more recently available drug classes, expanded guidance on management of coinfections (including tuberculosis, hepatitis B and hepatitis C) and additional emphasis on the needs of adolescents as they approach transition to adult services. There is a new section on the current ART 'pipeline' of drug development, a comprehensive summary table of currently recommended ART with dosing recommendations. Differences between PENTA and current US and World Health Organization guidelines are highlighted and explained.